2018
DOI: 10.1093/icvts/ivy073
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial permanent pacemaker implantation in the retrosternal space of a 2.3-kg infant

Abstract: Permanent pacemaker implantation in small infants can be challenging because of patient size and expected somatic growth. In our case, we used the retrosternal space as a generator pocket for an extremely low-birth-weight premature baby with autoantibody-associated congenital heart block born to a systemic lupus erythematosus mother.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…To prevent pacemaker generator complications, some authors have suggested inserting the generator in the subcutaneous tissue at the level of the upper quadrant, the external rib cage, or the space between the scapular muscles [2,3]. If rectus sheath seems to be too thin to endure the weight of the generator or another abdominal procedure is required, putting the generator under the sternum or in the thoracic cavity can be also an option [5]; nonetheless, we must consider airway obstruction due to external compression of the pacemaker generator, which is similar to the first complication described in this case study. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent pacemaker generator complications, some authors have suggested inserting the generator in the subcutaneous tissue at the level of the upper quadrant, the external rib cage, or the space between the scapular muscles [2,3]. If rectus sheath seems to be too thin to endure the weight of the generator or another abdominal procedure is required, putting the generator under the sternum or in the thoracic cavity can be also an option [5]; nonetheless, we must consider airway obstruction due to external compression of the pacemaker generator, which is similar to the first complication described in this case study. Fig.…”
Section: Discussionmentioning
confidence: 99%